توحید اسماء وصفات اورآثار صحابہ: تحقیقی جائزہ : A Research review on Asaar e Sahaba related to Toheed e Asma and Toheed e Sifaat (Al-Aasar, 2025)
This study delves into the fundamental principles of Touheed Asma o Siffat  (rules of purification) and examines the significant contributions of the Sahaba (companions) of the Prophet Muhammad, known as Asar-e-Sahaba, in shaping Islamic purification practices. Through a comprehensive analysis of primary Islamic sources, including the Quran, Hadith, and scholarly interpretations, this research aims to elucidate the theological, historical, and practical aspects of purification rituals in Islam. By exploring the teachings and actions of the Sahaba, this study seeks to highlight their role in preserving and disseminating the prophetic traditions related to cleanliness and purification. Furthermore, it investigates the contemporary relevance and application of Touheed Asma o Siffat and Asar-e-Sahaba in Muslim communities worldwide, shedding light on their enduring significance in Islamic jurisprudence and daily life. Through this exploration, this research contributes to a deeper understanding of Islamic purification practices and the invaluable legacy of the Prophet's companions in shaping Islamic traditions.